On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Race, cultures, identités : une approche féministe et postcoloniale - Bentouhami, Hourya (Philosophies, 2015)
La race fut longtemps appréhendée dans un sens biologique,approche qui constitue l'une des formes les plus puissantes de l'idéologie raciste. À la suite de la disqualification scientifique et politique de ces catégorisations biologiques, le racisme fut relégué au rang de simple préjugé. Ou, qu'en est-il de la production continuée de la race à l'ère prétendument "post-raciale" ? En mélangeant une approche féministe , attentive à une compréhension des rapports sociaux de sexe, et une approche postcoloniale , l'ouvrage analyse les conditions historiques et épistémologiques de la production de la race dans des sociétés qui se sont constituées - politiquement et économiquement - sur l'esclavage et la colonisation. Il montre que le racisme n'a pas disparu et a pris, au gré du renouvellement des formes de l'économie mondialisée, une nouvelle configuration qui oblige à nous interroger sur la supposée opposition entre un racisme biologique et un racisme dit culturel, qui aurait entériné l'inexistence des races biologiques, mais selon lequel il y aurait des différences culturelles irréductibles entre les peuples.
Keywords: approches et analyses; cours; discipline; fem1000; féminisme postcolonial; histoire et politique; inégalités; philosophie; premier cycle; privilèges; racisme; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Notes toward a performative theory of assembly - Butler, Judith (Harvard University Press, 2015)
Judith Butler elucidates the dynamics of public assembly under prevailing economic and political conditions, analyzing what they signify and how. Understanding assemblies as plural forms of perfomative action, Butler extends her theory of performativity to argue that precarity - the destruction of the conditions of livability - has been a galvanizing force and theme intoday's highly visible protests.
Keywords: approches et analyses; corps; discipline; genre; inégalités; militance; performativité; philosophie; précarité; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques

Traite, prostitution, inégalité - MacKinnon, Catharine A. (Collection Mobilisations, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

The promise of happiness - Ahmed, Sara (Duke University Press, 2010)
« The Promise of Happiness is a provocative cultural critique of the imperative to be happy. It asks what follows when we make our desires and even our own happiness conditional on the happiness of others: 'I just want you to be happy', 'I'm happy if you're happy'. Combining philosophy and feminist cultural studies, Sara Ahmed reveals the affective and moral work performed by the 'happiness duty', the expectation that we will be made happy by taking part in that which is deemed good, and that by being happy ourselves, we will make others happy. Ahmed maintains that happiness is a promise that directs us toward certain life choices and away from others. Happiness is promised to those willing to live their lives in the right way. Ahmed draws on the intellectual history of happiness, from classical accounts of ethics as the good life, through seventeenth-century writings on affect and the passions, eighteenth-century debates on virtue and education, and nineteenth-century utilitarianism. She engages with feminist, antiracist, and queer critics who have shown how happiness is used to justify social oppression, and how challenging oppression sometimes causes unhappiness. Reading novels and films including "Mrs. Dalloway", "The Well of Loneliness", "Bend It Like Beckham", and Children of Men, Ahmed considers the plight of the figures who are challenged by, and themselves challenge, the attribution of happiness to particular objects or social ideals: the feminist killjoy, the unhappy queer, the angry black woman, and the melancholic migrant. Through her readings, she raises critical questions about the moral order imposed by the injunction to be happy. »--Quatrième de couverture.
Keywords: approches et analyses; bonheur; care; discipline; inégalités; philosophie; queer; racisme; représentations; sciences humaines; sexisme; systèmes d'oppressions; thématiques; études culturelles